An experimental study of the production of biofuel from Lyngbyasp algae - Abbas, Abbas Mohsin; Elkheralla, Roaa Jafar; Abd Ali, Abbas Talib; Jebur, Assala Salam; Shwayel, Iman H.; Jayp, M. R. (University of Thi-Qar Journal of Science, 2024)
Global energy consumption is steadily rising, and fossil fuels are nonrenewable energy sources which provide the majority of this energy. Researchers are seeking and supporting renewable energy sources in order to balance supply and increasing demand. Microalgae is seen as an emerging and dependable feedstock that has the potential to displace fossil fuel-based sources of renewable energy among other options.In the present investigation, none dible hazardous oils from lyngbya sp. algae have been selected for the use as a feedstock for the biofuel production.Themicroalgal isolateswere identified based on their surface morphology under microscope. The biofuel was produced by the transesterificationreaction.Using Fourier-transform infrared spectroscopy (FTIR) analysis, the generated biofuel was characterized and the conversion was calculated.The findings imply that lyngbya sp. algal biomasses are y suitable for the generation of biofuel. More experimental investigations are required in this field.